Factors Influencing Emergence of Juveniles from Cysts of Heterodera zeae - Hashmi, S (Journal of nematology, 1995)
Several factors were studied to determine their effects on hatch and emergence of second-stage juveniles (J2) from cysts of Heterodera zeae. The optimum temperature for emergence of J2 from cysts of H. zeae was 30 C. No juveniles emerged from cysts at 10 or 40 C. Immersion of cysts in 4 mM zinc chloride solution stimulated 10% greater emergence of J2 than occurred in tap water controls during 28 days. Fresh corn rhizosphere leachates from 25-day and older plants growing in sand or sandy field soil stimulated 22-24% greater emergence of J2 from cysts than occurred in tap water after 28 days. Rhizosphere leachates stored for 30 days at 4 C and leachates of sand, sandy field soil, and silty field soil inhibited emergence of J2 from cysts by 7-12% compared to tap water. Rhizosphere leachates from corn plants aged 20, 30, 40, 50, or 60 days growing in sandy field soil stimulated emergence of J2 from cysts. Similar numbers of J2 emerged from cysts regardless of whether the source of cysts was field microplot cultures, greenhouse cultures, or growth chamber cultures. Fertilizing growth chamber cultures of H. zeae on corn plants resulted in a doubling of the numbers of cysts produced in the cultures, and those cysts yielded 2-3 times as many emerged J2 in hatching tests compared to cysts from similar unfertilized cultures